Determinants of conventional and Islamic banks profitability in Malaysia: evaluation of internal factors / Nur Faizah Mohd Yusof - Mohd Yusof, Nur Faizah (Faculty of Business Management, UiTM Johor, 2017)
The issue regarding measuring and managing the bank performance are always on the agenda due to critically important roles of the bank. The purpose of this study is to compare the profitability between the conventional and Islamic bank in Malaysia. Furthermore, the researcher also wants to find the relationship between the factors towards the conventional and Islamic bank in Malaysia. Thus, find out the most factors that give the huge impacts on the banks profitability. The profitability of the bank is being measured by dependent variables which is return on asset (ROA) and influenced by the independent variables such as banks size, deposit ratio, capital adequacy, management efficiency and financial leverage. Based on findings shows that Islamic bank is more profitable than conventional bank. The findings also supported by Ibrahim (2015) and Ramlan & Adnan (2016) both result showed that Islamic banks is more profitable compared to conventional banks on overall performance by using z-score test and regression test respectively. The study is carried out over 5 year's period that is from 2012 to 2016. The method of this study referred to F-test model, correlation and regression. From this study, we used secondary data and the data are collected from selected bank website in Malaysia. We used sample of 6 conventional banks and 6 Islamic banks established in Malaysia. Thus, the analysis of this paper can be used by the bank managers, investors, customers to make an evaluation of internal factors that can affect the bank's profitability.